Dinamika Qalb Dalam Perspektif Tafsir Dan Hadis Implikasi Terhadap Kesehatan Mental Dan Terapi Spiritual - Bilqis Malikatul Lutfiya; Mira Dwi Adhelia; Muhammad Saiful Rijal (PT. Padang Tekno Corp, 2026)
This study discusses the dynamics of qalb (the heart )from the perspectives of qur’anic exegesis (tafsir) and hadith, with an emphasis on its influence on mental health and spiritual healing. The purpose of this research is to explore the function of qalb as the core of consciousness, identify various forms of spiritual and psychological disturbances (diseases of the heart), and analyze tazkiyah (self-purification) as a therapeutic method. The methodology employed is qualitative research using a library research approach, involving the analysis of both classical and modern tafsir literature as well as relevant hadith sources. The findings indicate that qalb serves not only as a spiritual organ but also as a center of thought, emotion, and moral awareness. Disturbances of the qalb, such as doubt, hypocrisy, and spiritual negligence, are closely associated with mental health issues including anxiety, restlessness, and loss of life purpose. Furthermore, the concept of tazkiyah through remembrance of god (dhikr), repentace, introspection, and ethical practice provides a comprehensive framework for spiritual healing and mental well-being. The integration of tafsir and hadith perspectives on the dynamics of qalb offers broad insights into human inner life and contributes significantly to contemporary discussions on mental health. Spiritual therapy based on tazkiyah can serve as an alternative or complementary approach inaddressing psychological problems, particularly within an Islamic context.